2021
DOI: 10.3389/fonc.2020.619010
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Anlotinib Combined With PD-1 Antibody for Third-Line or Further-Line Treatment of Patients With Advanced Non-Small-Cell Lung Cancer

Abstract: BackgroundBoth anlotinib and programmed death 1 (PD-1) monoclonal antibody (mAb) have been approved for the third line treatment of metastatic non-small cell lung cancer (NSCLC). However, the combination of these two standard therapies has not been investigated in third-line or further-line treatment of patients with advanced NSCLC.MethodsWe reviewed 22 patients with NSCLC who received anlotinib combined with PD-1 mAb therapy from July 2018 to October 2019 at Sir Run Run Shaw Hospital. Based on the baseline ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…Similarly, the combination of ICIs and antiangiogenic agents in our cohort also yielded greater PFS (HR, 0.41; 95% CI, 0.23-0.73) and OS (HR, 0.41; 95% CI, 0.19-0.87) than ICIs alone. Meanwhile, Zhai et al found that anlotinib combined with PD-1 inhibitors showed promising efficacy as a third-or further-line treatment for NSCLC (26). The combination treatment achieved a median OS of 17.3 months, which was similar to the OS of 15.97 months in the P+A group in our cohort.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, the combination of ICIs and antiangiogenic agents in our cohort also yielded greater PFS (HR, 0.41; 95% CI, 0.23-0.73) and OS (HR, 0.41; 95% CI, 0.19-0.87) than ICIs alone. Meanwhile, Zhai et al found that anlotinib combined with PD-1 inhibitors showed promising efficacy as a third-or further-line treatment for NSCLC (26). The combination treatment achieved a median OS of 17.3 months, which was similar to the OS of 15.97 months in the P+A group in our cohort.…”
Section: Discussionsupporting
confidence: 77%
“…The risk of disease progression or death was reduced by 81% [hazard ratio (HR) =0.19; 95% confidence interval (CI): 0.12-0.32; P<0.0001] (15,16). Tolerance and safety profiles were also favorable (15,16) and comparable to other studies (19)(20)(21).…”
Section: Introductionsupporting
confidence: 83%
“…Collectively, strong reasons exist to support the multidimensional synergetic effects of anlotinib combined with anti-PD-1 antibodies. In a series of prospective and observational studies, the encouraging efficacy data of anti-PD-1 antibody plus anlotinib have been reported ( 22 , 34 36 ). In this study, interim analysis after 2 cycles of treatment showed a CR rate (CRR) of 50% and an ORR of 100%, indicating that this regimen could induce a rapid remission in NKTL.…”
Section: Discussionmentioning
confidence: 99%